Thermography of Tuberculin Reactions in Cattle - Merkal, R. S. (1973)
The allergic reactions of dermal induration and hyperthermia were compared in tuberculin-hypersensitive calves. Tuberculins prepared from Mycobacterium avium, M. bovis, and M. paratuberculosis were administered intradermally and the responses were compared. The indurations from immediate and delayed hypersensitivity reactions were readily distinguishable, but the hyperthermic responses appeared to contain elements of both immediate and delayed hypersensitivity.